OPTIMALISASI PELAYANAN TENAGA KESEHATAN TERHADAP KUALITAS PELAYANAN PASIEN DI KLINIK RAWAT INAP AMPELGADING MEDICAL CENTRE KABUPATEN MALANG - Lestari, Asih Sri (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2024)
Service optimization of health workers is maximizing health workers service in give health care to patient. Health care is directly or indirectly activity which produce health services in accordance with community needs to overcome their health problems. Health service quality as consistent patient satisfaction by providing efficacious, effective and efficient health services in accordance with the latest clinical guidelines and standards, which fulfill patient needs and satisfy service providers. Service quality approach that is often used as a reference is the quality model with the SERVEQUAL (Service Quality) method which can be used to determine service quality. This model was developed with five dimensions of service quality, such as tangibles, reliability, responsiveness, assurance and empathy. This research was conducted using a qualitative approach with case studies. The collected data analyzed using descriptive methods. Based on results data collection with patient, patient family, health workers and management, AMC Clinic has succeeded in fulfilling the reliability, responsiveness and assurance dimensions very well. This can be shown by the satisfied informant about received health care by the patient and the patient's family. The empathy dimension still needs to be optimized again by periodically monitoring the patient's condition.